The Impact of Blood Glucose Levels on Acid-Fast Bacteria Conversion in Tuberculosis Patients with Diabetes Mellitus - Shahrul Rahman; Andhyka Libawardana Pulungan; Kebba S. Bojang (Universitas Muhammadiyah Semarang, 2022)
Background: Tuberculosis (TB) is an infectious disease caused by Mycobacterium tuberculosis. Pulmonary tuberculosis in DM sufferers will aggravate hyperglycemia and spur ketoacidosis. Objective: To determine the effect of blood glucose levels on the conversion of acid-fast bacteria (AFB) in TB patients with DMMethods: This research is descriptive-analytical with a retrospective cohort approach. The data are taken as data from TB patients with DM at the Pulmonary Hospital of North Sumatera Province from July 2018-September 2019. The sample is pulmonary tuberculosis-positive AFB patients with high blood glucose levels, which was carried out with total sampling. The sample used in the study was 49 patients who met the inclusion criteria. Results: There was that in the category of increased blood glucose levels with AFB converted by 4 (7.3%) respondents, while those who were not converted were 6 (2.7%) respondents. The category of decreased blood glucose levels with AFB was converted by 32 (28.7%) respondents, while 7 (10.3%) respondents were not converted. The p-value shows 0.014, which means the effect of blood glucose on the conversion of acid-fast bacteria has a significant relationship.Conclusion:There is a significant relationship between the effect of blood glucose levels on acid-fast bacteria conversion.